The Intersection of Epigenetics and Senolytics in Mechanisms of Aging and Therapeutic Approaches - Daiana Burdusel; Thorsten R. Doeppner; Roxana Surugiu; Dirk M. Hermann; Denissa Greta Olaru; Aurel Popa-Wagner (Biomolecules)
The biological process of aging is influenced by a complex interplay of genetic, environmental, and epigenetic factors. Recent advancements in the fields of epigenetics and senolytics offer promising avenues for understanding and addressing age-related diseases. Epigenetics refers to heritable changes in gene expression without altering the DNA sequence, with mechanisms like DNA methylation, histone modification, and non-coding RNA regulation playing critical roles in aging. Senolytics, a class of drugs targeting and eliminating senescent cells, address the accumulation of dysfunctional cells that contribute to tissue degradation and chronic inflammation through the senescence-associated secretory phenotype. This scoping review examines the intersection of epigenetic mechanisms and senolytic therapies in aging, focusing on their combined potential for therapeutic interventions. Senescent cells display distinct epigenetic signatures, such as DNA hypermethylation and histone modifications, which can be targeted to enhance senolytic efficacy. Epigenetic reprogramming strategies, such as induced pluripotent stem cells, may further complement senolytics by rejuvenating aged cells. Integrating epigenetic modulation with senolytic therapy offers a dual approach to improving healthspan and mitigating age-related pathologies. This narrative review underscores the need for continued research into the molecular mechanisms underlying these interactions and suggests future directions for therapeutic development, including clinical trials, biomarker discovery, and combination therapies that synergistically target aging processes.